2014
DOI: 10.2169/internalmedicine.53.2435
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Acute Myocardial Infarction following the Improvement of Influenza A(H1N1)pdm2009-related Acute Myocarditis

Abstract: A 52-year-old Indian man was hospitalized due to dyspnea and a high fever caused by influenza A(H1N1) pdm2009. Elevated cardiac enzymes, a chest X-ray showing bilateral infiltrative shadows, cardiomegaly and pleural effusion and echocardiography indicating diffuse hypokinesis of the left ventricle suggested cardiac failure due to acute myocarditis. Owing to the administration of combined modality therapy, including steroids and intravenous γ-globulin, the patient's clinical symptoms of influenza completely res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…There have been approximately 44 cases of influenza‐associated myocarditis in adult patients described in case reports and case series (Table ) . Among those reported, 52% (23/44) occurred in men and 68% (30/44) occurred in patients under 40 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…There have been approximately 44 cases of influenza‐associated myocarditis in adult patients described in case reports and case series (Table ) . Among those reported, 52% (23/44) occurred in men and 68% (30/44) occurred in patients under 40 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…In literature we found some case reports on rhythm disorders in swine flu like VF, AF, complete heart block, first degree heart block, bradycardia and wide complex tachycardia [13,14,16,20]. Although precise mechanisms by which ECG manifestations are produced in H1N1 influenza are still unknown it may be a direct cytolytic effect of virus on myocardial cells with cytotoxic immunologic interaction, ischemia due to intracapillary thrombosis, inflammatory edema pressing AV node and other conduction tissue or primarily affecting conduction tissue/AV nodal pacemaker cells resulting in resting membrane potential changes [13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study 4 patients developed STEMI, 2 of them were known case of pre-existing CAD and 2 were not (one 60 year old male and the other 64 year female), the values of Troponin I, NT-proBNP and CPK-MB in these 2 new cases was highly raised (778.2/7164/8.94 and 190.9/7016/6.3 respectively). It has been shown that influenza may precipitate MI [20,22,23]. It has also been observed that incidence…”
Section: Discussionmentioning
confidence: 99%
“…There were also 11 exacerbations COPD of and one case with severe myocarditis. Several studies have described myocarditis as a severe complicating form of influenza [ 17 , 18 ] and COPD is an independent risk factor for poor clinical outcomes in influenza and hospitalization in intensive care [ 19 ].…”
Section: Discussionmentioning
confidence: 99%